Manajemen Mutu Satuan Pendidikan: Analisis Terhadap Input, Proses, Output dan Outcome SMA Muhammadiyah Purwodadi - Suprojo D.S.; Sutama; Anam Sutopo (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Quality of Education is the ability or competence of Educational Institutions in utilizing and managing educational resources, which are used to improve students' learning abilities as optimally as possible. Quality education is education that is able to carry out the process of maturing the quality of students which is developed by freeing students from ignorance, incompetence, helplessness, unrighteousness, and from bad morals and faith. Since its inception, SMA Muhammadiyah Purwodadi has been committed to guaranteeing the quality of education units. Guarantees carried out thoroughly from the input, process, output, and outcome. The input of resources at SMA Muhammadiyah Purwodadi is very adequate in terms of quantity and quality, except for the interaction of students who are only sufficiently capable with a range of values ​​of 75.00-83.00. Analyzed from the process, SMA Muhammadiyah Purwodadi is committed to carrying out learning very well. The analysis was carried out at the learning preparation stage with the availability of learning administrative documents, the learning implementation process and the assessment process. Analysis of the output shows that a number of students who took part in education at the end of class XII have successfully passed 100%. Besides that, the achievements of the SMA Muhammadiyah Purwodadi students were also very encouraging. However, these achievements are not too significant for academic achievements. Judging from the outcome, on average almost 30% of SMA Muhammadiyah Purwodadi graduates are absorbed in tertiary institutions, both public and private universities. SMA Muhammadiyah Purwodadi does not yet have data on the achievements of its graduates while studying at tertiary institutions for the next outcome analysis process.